Selected Decisions (11th Ed). (Selected Decisions; Issue, Year, 1985)
This paper presents Selected Decisions and Selected Documents' Eleventh Issue of the IMF. This volume, the Eleventh Issue of Selected Decisions of the IMF and Selected Documents, presents the decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the IMF to which frequent reference is made in the current activities of the IMF. In addition, the volume contains certain documents relating to the IMF and the United Nations. With few exceptions, the decisions are of a general nature and relate to certain obligations, policies, and procedures under the Articles of Agreement. The issue contains most of the decisions published in the Tenth Issue and in the Supplement to that issue that remain in effect, as well as new decisions adopted after the publication of the Supplement. Decisions of the Fund that are incorporated in the By-Laws, Rules and Regulations are not reproduced in this volume.